Analisa Pemanfaatan E-Learning Menggunakan Data Statistik Pengguna Aplikasi Startup Pendidikan Selama Wabah Pandemi Covid-19 - Liszulfah Roza; Nurul Aulia; Zulherman Zulherman* (Universitas Syiah Kuala, 2021)
The changes that happened during the epidemic due to the Central Government's and the Ministry of Education and Culture's (Kemendikbud) closure of schools had a considerable impact on the learning models and methods followed by all Indonesian students. As a result, this policy implements a digital education or e-learning system implemented during the Covid-19 outbreak, requiring students to use the internet to supplement their home education. However, the public is not well informed about the use of free learning support applications. As a result, information from online learning applications and digital education is required, as these are used as educational support tools for all students. The purpose of this study is to examine how digital learning systems, or e-learning, are used by examining the statistical data of users of a widely used educational startup application. The Teacher Room, Zenius, and Quipper applications will be examined. The research method compares three educational applications used in Indonesia that rely on secondary data from www.similiarweb.com to ascertain the number of website visits and ranking. These findings contribute to the body of knowledge regarding digital learning systems during the Covid-19 outbreak